Improvement of production and quality research of bakery products enriched with iodine - Головко, Микола Павлович; Полупан, Валентин Вадимович; Бакіров, Мюшфік Панах огли; Колодій, Ілона Ігорівна (Technology audit and production reserves, 2015)
In view of the acute problem of iodine deficiency, which threatens by a number of pathological conditions of person, it is proved a necessity of creating mass consumption food products including bakery products rich in iodine compounds resistant to outside influence. With this purpose it is proposed improvements of bakery using iodine-protein additives containing stable iodine compounds, whose use is safe for the human body. It is proved the rationality of adding 1 % by weight of flour additives in the product that can compensate for 50 % of the daily requirement of iodine. Researches of organoleptic and physical and chemical parameters of quality of bakery products with iodine-protein additive require to carry the product to the rich products of highest grade in accordance with DSTU P-4585: 2006 "Rich bakery products. General specifications". Use the iodine-protein additive in content of bakery products allow compensate the lack of iodine and also to ensure high quality of end product.